Sistem Pendukung Keputusan Penerapan Metode MOOSRA dan Pembobotan ROC dalam Penilaian Kinerja Laboran Kimia - Deby Lorensyah Rambe; Ali Akbar Ritonga; Elysa Rohayani Hasibuan; Iwan Purnama (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Laboran is a designation for technical personnel who operate in a laboratory environment or a place related to scientific, research or testing activities. A chemical worker is a technical worker who has specific knowledge and skills in the chemical field. In schools, chemical workers have a role as workers who supervise and manage chemical laboratories. His main duties include sampling, material testing, data processing and maintenance of laboratory equipment. The school needs to know the performance of each chemical worker, so an assessment of the performance of each chemical worker is needed so that the school knows the best performance of the chemical worker, an additional salary will be added. The performance assessment includes several criteria namely Technical Expertise, Professional Ethics, Problem Solving, Punctuality, Safety and Health, Maintenance of tools and materials, Report Quality, Self-Development, Accuracy, Teamwork and Communication. To simplify the evaluation system for the performance of chemical workers and find out who is the best, a decision-making system is needed, namely a decision support system (DSS). SPK is a system designed to assist decision makers in solving problems or choosing the best option from various available alternatives. In this study the authors used the MOOSRA (Multi-Objective Optimization on the Basis of Simple Analysis) method and ROC (Rank Order Centroid) weighting. The MOOSRA method is a stable, consistent, and reliable multi-criteria comparison method that can provide an accurate assessment of chemical workforce performance. From the application of the ROC and MOOSRA methods, it was obtained an assessment of the performance of the chemical workforce with the chemical workforce alternative with the highest performance, namely the LK07 alternative on behalf of Gueen with a value of 207.95261.